Thermodynamics and activity coefficients at infinite dilution for organic solutes in the ionic liquid 1-hexyl-2, 3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide. (November 2016) - Ge, Ming-Lan; Zhang, Qin; Li, Sai-Nan; Li, Yin-Juan; Zhang, Xiu-Zhen; Mu, Zhao
Graphical abstract: Highlights: Measurements of activity coefficients at infinite dilution using GLC. The (gas-liquid) partition coefficients were calculated. The excess thermodynamic functions, entropies, and Gibbs energies were calculated. The solubility parameter of the IL [HMMIM][NTf2 ] was determined by two methods. Selectivity and capacity for hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). Abstract: Activity coefficients at infinite dilution ( γ i ∞ ) and gas-liquid partition coefficients ( K L ) for organic solutes: n -alkanes, alkenes, alkyl benzenes, acetonitrile, acetone, tetrahydrofuran, ethyl acetate, and chloromethanes in the ionic liquid (IL) 1-hexyl-2, 3-dimethylimidazolium bis(trifluoromethylsulfonyl)imide ([HMMIM][NTf2 ]) have been measured by the gas-liquid chromatographic method (GLC) in the temperature range of (313.15–353.15) K. The thermodynamic functions at infinite dilution as partial molar excess enthalpies at infinite dilution ( H ‾ i E, ∞ ) were derived from the temperature dependence of the γ i ∞ values. Gibbs energies ( G ‾ i E, ∞ ) and entropies ( T ref S ‾ i E, ∞ ) of organic solutes in [HMMIM][NTf2 ] at a reference temperature T ref  = 298.15 K were also calculated from the γ i ∞ values. The solubility parameters of the IL [HMMIM][NTf2 ] were determined by two methods. Selectivity ( S ij ∞ ) and capacity ( k j ∞ ) at infinite dilution at 323.15 K have been determined for n -hexane ( i )/benzene ( j ), cyclohexane ( i )/benzene ( j ). The results were analyzed in comparison to literature data for alkylimidazolium-based ILs with [NTf2 ] − . For three isomeric xylenes separation problems, selectivity at 323.15 K were also obtained from the γ i ∞ values.